DRYING OF PARSLEY LEAVES IN A SOLAR DRYER AND UNDER OPEN SUN: MODELING, ENERGY AND EXERGY ASPECTS - Akpinar, E. Kavak (Wiley, 2011)
In this study, the thin layer drying characteristics in a solar dryer with forced convection and under open sun with natural convection of parsley was investigated, and energy analyses and exergy analyses of the solar drying process of parsley were performed. The drying data were fitted to the 10 different mathematical models. Among the models, the Wang and Singh model for the forced solar drying and the natural open sun drying were found to best explain thin layer-drying behavior of parsley. Using the first law of thermodynamics, the energy analyses throughout the drying process were estimated. However, exergy analyses during the drying process were determined by applying the second law of thermodynamics. Energy utilization ratio (EUR) values of the drying cabinet varied in the ranges between 8.57-41.56%. The values of exergy inflow and exergy outflow were found to be in the range of 0.263-0.680 kJ/kg and 0.187-0.378 kJ/kg, respectively. The values of exergy loss and exergy efficiency were found to be in the range of 0.0347-0.399 kJ/kg and 35.76-86.79%, respectively. EUR decreased with increasing drying time while exergy efficiency increased. PRACTICAL APPLICATIONS Drying is widely used in a variety of thermal energy applications ranging from food drying to wood drying. Drying can either be done by traditional sun drying or industrially, through the use of solar dryers or hot-air drying. The solar dryers could be an alternative to the hot-air drying and open sun drying methods, especially in locations with good sunshine during the harvest season. This study is useful not only for producers of dry parsley, but also for all producers of dry herbs. It may be successfully used in the design, modeling, analysis and performance evaluation of solar and sun drying.
Keywords: Rice